Evaluation of the AGNES Climate Governance, Diplomacy and Negotiations Leadership Program - Szilagyi, Lili; Arum, Shadrack (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
This report presents an evaluation of the climate leadership program run by the African Group of Negotiators Experts Support (AGNES), presenting evidence on the participants' experience of the program.